Quo Vadis, Medicus? Health Behaviour Among Health Professionals and Students - Laudanska-Krzeminska, Ida (De Gruyter, 2015)
The book discusses the health condition of Polish current and future health professionals. The study was conducted on around 800 medical staff members (in-training and professional). The author analyses nutrition behaviour, physical activity, smoking, drinking alcohol and their psycho-social determinants (health self-assessment, value of health, health locus of control, health related self-efficacy). The educational and behavioural needs of the investigated group depend on career stage and profession. As a result, there is a need for health promotional programs targeting carefully chosen medical staff groups, with an emphasis on their special health needs. The expectation that physicians or other medical professionals will heal themselves proves to be futile in this part of Europe. This should be a starting point in a discussion about the role of health providers in modelling health behaviours and health promotion counselling for their patients. Reflection is needed especially among health related professionals in different institutions (e.g., universities, schools, hospitals), health societies and non-profit organisations involved in health promotion, insurance and health companies.